Anxious people eaudiobook A novel. - Backman, Fredrik (Simon & Schuster Audio, 2020)
An instant #1 New York Times bestseller, the new novel from the author of A Man Called Ove is a "quirky, big-hearted novel... .Wry, wise, and often laugh-out-loud funny, it's a wholly original story that delivers pure pleasure" ( People ). Looking at real estate isn't usually a life-or-death situation, but an apartment open house becomes just that when a failed bank robber bursts in and takes a group of strangers hostage. The captives include a recently retired couple who relentlessly hunt down fixer-uppers to avoid the painful truth that they can't fix their own marriage. There's a wealthy bank director who has been too busy to care about anyone else and a young couple who are about to have their first child but can't seem to agree on anything. Add to the mix an eighty-seven-year-old woman who has lived long enough not to be afraid of someone waving a gun in her face, a flustered but still-ready-to-make-a-deal real estate agent, and a mystery man who has locked himself in the apartment's only bathroom, and you've got the worst group of hostages in the world. Each of them carries a lifetime of grievances, hurts, secrets, and passions that are ready to boil over. None of them is entirely who they appear to be. And all of them—the bank robber included—desperately crave some sort of rescue. As the authorities and the media surround the premises, these reluctant allies will reveal surprising truths about themselves and set in motion a chain of events so unexpected that even they can hardly explain what happens next. Proving once again that Backman is "a master of writing delightful, insightful, soulful, character-driven narratives" ( USA TODAY ), Anxious People "captures the messy essence of being human....It's clever and affecting, as likely to make you laugh out loud as it is to make you cry" ( The Washington Post ). This "endlessly entertaining mood-booster" ( Real Simple ) is proof that the enduring power of friendship, forgiveness, and hope can save us—even in the most anxious of times.